Digitalisasi Tabayyun Ethics 2.0: Revitalisasi Nilai Qur’ani dalam Menangkal Hoaks di Era Transformasi Digital - Farah Fadia Ferdayanti; Arif Dika Prasetya (Kartika: Jurnal Studi Keislaman, 2026)
Digital transformation has changed the patterns of social communication while simultaneously accelerating the spread of information in the public sphere. On the other hand, technological advancement has also triggered an increase in the spread of hoaxes, which potentially cause social unrest, conflict, and a decline in public trust in information. This study aims to examine the value of tabayyun in the Qur’an as an ethical foundation for addressing the spread of hoaxes in the digital era and to formulate the concept of Digital Tabayyun Ethics (DTE) 2.0 as a model of media ethics based on Qur’anic values. This research employs a qualitative method using a library research approach. Primary data sources are derived from the Qur’an and classical and contemporary tafsir (Qur’anic exegesis), particularly the interpretation of QS Al-Hujurat verse 6. Meanwhile, secondary sources include books, articles, academic journals, and other relevant documents related to digital literacy and information ethics. The data were analyzed using a descriptive-analytical method through interpretation of the verse, examination of its socio-historical context, and its relevance to contemporary digital information dynamics. The results show that the concept of tabayyun has strong relevance as a principle of information verification in addressing hoaxes. Through the development of Digital Tabayyun Ethics (DTE) 2.0, the value of tabayyun is actualized into four main principles: verification before viral, validation of information, accountability of digital speech, and empathy in communication. These principles form a Qur’anic digital ethics framework that emphasizes honesty, responsibility, and prudence in disseminating information in the era of digital transformation